Using psychometric ability to improve education in ultrasound‐guided regional anaesthesia: a multicentre randomised controlled trial. (18th January 2021) - Chuan, A.; Jeyaratnam, B.; Iohom, G.; Shorten, G.; Lee, P.; Miglani, S.; Kwofie, K.; Szerb, J.; Niazi, A. U.; Jin, R.; Jen, T.; McCartney, C. J.; et al.
Summary: The learning curve for novices developing regional anaesthesia skills, such as real‐time ultrasound‐guided needle manipulation, may be affected by innate visuospatial ability, as this influences spatial cognition and motor co‐ordination. We conducted a multinational randomised controlled trial to test if novices with low visuospatial ability would perform better at an ultrasound‐guided needling task with deliberate practice training than with discovery learning. Visuospatial ability was evaluated using the mental rotations test‐A. We recruited 140 medical students and randomly allocated them into low‐ability control (discovery learning), low‐ability intervention (received deliberate practice), high‐ability control, and high‐ability intervention groups. Primary outcome was the time taken to complete the needling task, and there was no significant difference between groups: median (IQR [range]) low‐ability control 125 s (69–237 [43–600 s]); low‐ability intervention 163 s (116–276 [44–600 s]); high‐ability control 130 s (80–210 [41–384 s]); and high‐ability intervention 177 s (113–285 [43–547 s]), p = 0.06. No difference was found using the global rating scale: mean (95%CI) low‐ability control 53% (95%CI 46–60%); low‐ability intervention 61% (95%CI 53–68%); high‐ability control 63% (95%CI 56–70%); and high‐ability intervention 66% (95%CI 60–72%), p = 0.05. For overall procedure pass/fail, the low‐ability control group pass rate of 42% (14/33) was significantly less than the other three groups: low‐ability intervention 69% (25/36); high‐ability control 68% (25/37); and high‐ability intervention 85% (29/34) p = 0.003. Further research is required to determine the role of visuospatial ability screening in training for ultrasound‐guided needle skills.